Parasitaemia among Patients and Blood Donors in Ijebu-North, Southwest Nigeria - A, Agbolade; Akinmoladun, A; Abimbola, W.A.; Raufu, S. T.; Atanda, O. M.; Akinyemi, S. F. (Asian Journal of Biological and Life Sciences, 2013)
There is a persistent risk of passive transmission of a number of haemoparasites through blood transfusion in tropical Africa. Parasitaemia was studied among patients and blood donors in Ijebu-Igbo, and Ago-Iwoye, Ijebu-North, Southwest Nigeria. Atotal of 485 patients studied retrospectively (for the period between July 2006 and July 2007), and 237 other patients (between August 2007 and January 2008) were examined using Giemsa - stained thin blood films, while 100 apparently healthy self-selected blood donors (between February and April 2008) were examined using thin and thick blood films stained with Field stain and buffered Giemsa stain, respectively. 82.9% of the patients studied retrospectively and 89.9% of the other group of patients examined had Plasmodium parasitaemia, but the infection was neither gender-dependent nor age-dependent in both groups. 45.0% of the blood donors had Plasmodium parasitaemia which was statistically higher in males (51.3 %) than in females (20.0 %) (P < 0.001) and statistically highest in 20-30 years age group ((P < 0.001). 14% and 1% of the blood donors had Trypanosoma and microfilariae of Wuchereria bancrofti, respectively. Atotal of 230 out of the patients examined between August 2007 and January 2008 were interviewed. 68.7% (158) of them had mosquito bites in the previous one month and were Plasmodium parasitaemia positive. 86.9% (172 / 198) of those that used mosquito nets and/or insecticides were Plasmodium parasitaemia positive, which was statistically higher than 13.1% (26 / 198) who were negative (P< 0.001). The findings of this study underscore the need for the formulation, effective implementation and monitoring of policies that will ensure safe blood transfusion in the study area.